Comparative phytochemical studies on the roots of Polygala azizsancarii and P. peshmenii and neuroprotective activities of the two xanthones - Calis, Ihsan; Becer, Eda; Unlu, Ayse; Aydin, Zubeyde Ugurlu; Hanoglu, Azmi; Vatansever, H. Seda; Donmez, Ali A. (Pergamon-Elsevier Science Ltd, 2023)
Six known sucrose mono-, di- and triesters and five xanthone derivatives were isolated from the roots of Polygala peshmenii Eren, Parolly, Raus & Kurschner which is a narrow species endemic to Turkiye. Among the xanthones, 1,7-dihydroxy-2,3-methylenedioxy-5,6-dimethoxy-xanthone is an undescribed compound isolated for the first time from a natural source. The studies on the roots of P. azizsancarii Do & BULL;nmez have resulted in the isolation of four known compounds including sucrose mono-, di- and triesters. The structures of the sucrose esters and xanthones isolated from P. azizsancarii and P. peshmenii were established by spectroscopic methods, including 1DNMR (1H NMR, 13C NMR, DEPT-135), 2D-NMR (COSY, NOESY, HSQC, HMBC). Neuroprotective activities of two xanthones, 1,3,6-trihydroxy-2,5,7-trimethoxyxanthone and 3-O-& beta;-D-glucopyranosyloxy-1,6-dihydroxy-2,5,7-trimethoxyxanthone isolated from the roots of P. azizsancarii were evaluated in vitro using in a cellular model of Alzheimer's disease. SKNAS human neuroblastoma cells were used in the study and treated with different consecrations of A & beta;25-35 oligomer for up to 48 h. Cell viability was evaluated using MTT assay. The distribution of & beta;-amyloid, & alpha;-synuclein, tau, JAK2, STAT3, caspase 3 and BMP-2 were investigated using indirect immunoperoxidase staining. Our results suggested that both xanthones control tau aggregation with no effect on & beta;-amyloid plaque formation. In addition, for neuronal pathophysiology in AD cell model, decreased distributions of JAK/ STAT3 and BMP2 signaling pathways were demonstrated, therefore they play a role in the protective effect on neurons in neurodegenerative disease. A significant decrease in caspase 3 immunoreactivity was detected after the administration of both compounds in AD cells. Therefore, both compounds control neuronal pathophysiology and rescue cell death in AD disease.
Keywords: Polygala azizsancarii; Polygala peshmenii; Polygalaceae; Xanthones; Sucrose esters; Neuroprotective activity